Painful generalised clonic and tonic-clonic seizures with retained consciousness. Issue 6 (1st December 1997) - Bell, William L; Walczak, Thaddeus S; Shin, Cheolsu; Radtke, Rodney A
Abstract : Two patients in whom consciousness and memory were retained during bilateral clonic or tonic-clonic seizures are reported on, and three patients reported on previously are reviewed. Ictal semiology differed from myoclonic and supplementary motor seizures, which are other seizure types characterised by bilateral motor movements and retained awareness. In the two new patients ictal pain was a prominent feature. It is proposed that propagation of seizure activity may be confined to the sensorimotor areas bilaterally while sparing the neural structures involved in maintaining consciousness and in processing language and memory. This unusual type of seizure may be misdiagnosed as a pseudoseizure. Detailed description of the ictal events and further laboratory evaluation including video-EEG monitoring may be necessary to make the distinction.